Characterization of the Cation‐Binding Capacity of a Potassium‐Adsorption Filter Used in Red Blood Cell Transfusion. Issue 3 (6th February 2015) - Suzuki, Takao; Muto, Shigeaki; Miyata, Yukio; Maeda, Takao; Odate, Takayuki; Shimanaka, Kimio; Kusano, Eiji
Abstract A K+‐adsorption filter was developed to exchange K+ in the supernatant of stored irradiated red blood cells with Na+. To date, however, the filter's adsorption capacity for K+ has not been fully evaluated. Therefore, we characterized the cation‐binding capacity of this filter. Artificial solutions containing various cations were continuously passed through the filter in 30 mL of sodium polystyrene sulfonate at 10 mL/min using an infusion pump at room temperature. The cation concentrations were measured before and during filtration. When a single solution containing K+, Li+, H+, Mg2+, Ca2+, or Al3+ was continuously passed through the filter, the filter adsorbed K+ and the other cations in exchange for Na+ in direct proportion to the valence number. The order of affinity for cation adsorption to the filter was Ca2+>Mg2+>K+>H+>Li+. In K+‐saturated conditions, the filter also adsorbed Na+. After complete adsorption of these cations on the filter, their concentration in the effluent increased in a sigmoidal manner over time. Cations that were bound to the filter were released if a second cation was passed through the filter, despite the different affinities of the two cations. The ability of the filter to bind cations, especially K+, should be helpful when it is used for red blood cell transfusion at the bedside. The filter may also be useful to gain a better understanding of the pharmacological properties of sodium polystyrene sulfonate.